The Wartime Book Club - Thompson, Kate, 1974- (Forever, 2024)
"The Isle of Jersey was once a warm and neighborly community, but in 1943, German soldiers patrol the cobbled streets, imposing a harsh rule. Nazis have ordered Grace La Mottée, the island's only librarian, to destroy books that threaten the new regime. Instead, she hides the stories away in secret. Along with her headstrong best friend, she wants to fight back. So she forms the Wartime Book Club: a lifeline, offering fearful islanders the joy and escapism of reading. But as the occupation drags on, the women's quiet acts of bravery become more perilous - and more important - than ever before. And when tensions turn to violence, they are forced to face the true, terrible cost of resistance."--